Quantitative analysis of the selection involving progenies of maize (Zea mays L.) in soils under "cerrado" and fertile. I. Genetic gains - Vilela de Resende, Marcos Deon; Lopes de Souza Júnior, Claudio; Gomes e Gama, Elto Eugênio; Magnavaca, Ricardo (Pesquisa Agropecuaria Brasileira, 1997)
This paper reports results from the evaluation of half-sib progenies of the maize variety BR 108 in soils under "cerrado" and fertile. Estimates of the additive genetic variance showed that the genetic variability in the "cerrado" for ear weight was smaller than that in the fertile soil. The genetic variability in the "cerrado" was null for prolificacy. Estimates of the genotype x environment interaction were negligible for plant and ear height, days tasseling and prolificacy. Genotype x environment interaction was high for ear weight, with low genetic correlation between progeny means at the two environments. The genetic gains showed that for ear weight the indirect (selection in one environment and response in another) presents low efficiency. Aiming to obtain gains in the "cerrado", the selection must be practised in the "cerrado" or in the average of the two environments. To enhance the mean productivity the best alternative is to select on the average of the two environments or on the fertile when is not possible to test the progenies in the two environments. For plant and ear height and days to tasseling, the selection can be practised in any environment. For prolificacy, selection is possible only in the fertile soils.
Keywords: genotype x environment interaction; genetic parameters; acid soils; selection response